277 RACIAL/ETHNIC DISPARITIES IN PEDIATRIC ASTHMA ADMISSION SEVERITY AND HOSPITAL UTILIZATION. (1st January 2006) - Teufel, R. J.; Basco, W. T.; Darden, P. M.
Abstract : Background: Asthma is an ambulatory care-sensitive condition, one in which hospital admission can be avoided with adequate preventive medical care. Black and Hispanic children have less access to preventive care than nonminorities. Objective: To examine inpatient pediatric admission severity, hospital utilization, and mortality for evidence of racial/ethnic disparities. Methods: Data from the 2000 Healthcare Cost and Utilization Project Kids Inpatient Database (HCUP KID), a national inpatient sample, were used to examine hospital admissions for children 0-18 yrs admitted with a primary discharge diagnosis of asthma. Admission severity is defined as emergent or nonemergent. Hospital utilization is defined by length of stay (LOS) and total charges. Mortality is defined as inpatient mortality. Race/ethnicity is defined as white, black, Hispanic, and other. LOS and total charge are reported as means. Bivariable associations between race/ethnicity were assessed using chi-square tests and simple linear regression for categorical and continuous variables, respectively. The analysis accounted for complex sample design. Results: Asthma accounted for 5.8% of all pediatric non-newborn admissions in 2000. Black children were more likely to be admitted emergently than white children (64% vs 44%; p < .001, respectively). Total charges were greater for BLACK children and Hispanic children compared to white children ($6, 030 and $7, 640 vs $5, 220; both p < .001, respectively). LOS was greater for black and Hispanic children as compared to white children (2.40 days and 2.61 days vs 2.27 days; both p < .001, respectively). Inpatient mortality for asthma was rare at 0.05% and not associated with race/ethnicity (p = .2). Conclusions: Racial/ethnic disparities exist for pediatric asthma admissions. Minority children are admitted emergently more often and have increased hospital utilization per admission as compared to white children. These differences are potentially a result of different access to medical care.